A lithium-modified zirconium-based metal organic framework (UiO-66) for efficient CO2 adsorption. (15th November 2018) - Niu, Zhaodong; Guan, Qingqing; Shi, Yuzhen; Chen, Yuan; Chen, Qiuling; Kong, Zhaoni; Ning, Ping; Tian, Senlin; Miao, Rongrong
Abstract : The adsorption mechanism of carbon dioxide (CO2 ) on Li/UiO-66 was studied by an in situ DRIFTS study. Abstract : This report puts forward an economically-feasible method for the preparation of a novel lithium doped metal–organic framework ( i.e., Li/UiO-66). UiO-66 was impregnated with an ethanol solution of lithium nitrate instead of expensive and toxic organolithium. Lithium nitrate was used as the alkali-metal resource for the modified MOFs. The samples were characterized by XRD, FTIR, XPS, BET, etc. The results indicated that free carboxylate protons can be replaced by the doped lithium cations and the formed lithium carboxylate groups. The effect of the doped lithium on CO2 adsorption and separation was evaluated by gas sorption isotherm measurements. Moreover, the interaction between adsorbed CO2 and the MOFs was studied by in situ diffuse reflectance infrared Fourier transform spectroscopy ( in situ DRIFTS). The in situ DRIFTS results showed that the doped lithium can increase the concentration of the active metal sites, which can provide some new adsorption sites for CO2 .